2016
DOI: 10.4103/0970-9185.182108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone in low volume supraclavicular brachial plexus block: A double-blinded randomized clinical study

Abstract: Background and Aims:With the use of ultrasound, a minimal effective volume of 20 ml has been described for supraclavicular brachial plexus block. However achieving a long duration of analgesia with this minimal volume remains a challenge. We aimed to determine the effect of dexamethasone on onset and duration of analgesia in low volume supraclavicular brachial plexus block.Material and Methods:Sixty patients were randomly divided into two groups of 30 each. Group C received saline (2 ml) + 20 ml of 0.5% bupiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Further, Alarasan et al. () also found no statistically significant differences in the onset of sensory and motor block when dexamethasone was used as an adjuvant to bupivacaine in supraclavicular brachial plexus block.…”
Section: Discussionmentioning
confidence: 98%
“…Further, Alarasan et al. () also found no statistically significant differences in the onset of sensory and motor block when dexamethasone was used as an adjuvant to bupivacaine in supraclavicular brachial plexus block.…”
Section: Discussionmentioning
confidence: 98%
“…The addition of dexamethasone to regional anesthetics such as lidocaine, bupivacaine, and other sodium channelblocking anesthetics has been shown to prolong the duration of analgesia. 5,11,[32][33][34][35][36][37] Recently, a meta-analysis of nine randomized trials by Choi et al 1 found that the addition of dexamethasone to regional anesthetics prolongs the duration of analgesia by approximately six hours. Furthermore, they reported a trend towards decreased opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing duration of local anesthetic action is desired for prolongation of postoperative patient comfort, as well as decreasing perioperative opioid consumption and subsequent side effects. Many adjuvants to local anesthetics such as epinephrine, clonidine,[ 1 ] tramadol, opioids,[ 2 ] dexmedetomidine, and neostigmine have been studied in brachial plexus block, but each drug has its own side effects,[ 3 ] and analgesic effect extends only up to early postoperative period. Recently, dexamethasone,[ 4 ] a glucocorticoid, when used as an adjuvant to local anesthetics in brachial plexus block has been found to have prolonged postoperative analgesia and a favorable side effect profile.…”
Section: Discussionmentioning
confidence: 99%